Com quantas armas se faz uma Sociedade"Civil "?: controles sobre armas de fogo na governança global, Brasil e Portugal (1995 -2010) - Luciana Maria de Aragao Ballestrin (2010)
The present study originated from the observation of three correlated phenomena occurring in various parts of the world in the last two decades: the increase of violent conflicts among civilians, the growth of firearm restriction policies at the regional, national and global levels and the attention civil society organizations paid to the problem of armed violence. The first two findings are related to the inundation of small arms and light weapons in the civil sphere with the end of the Cold War (1945-1991). The third finding is related to civil societys capacity of bringing the issue of the monopoly of arms and the legitimate control over the means of violence, which historically has belonged to the State, to diverse public spheres. Considering the manner in which the issue of firearms control arose in Global Governance, Brazil and Portugal, this thesis sought to explore the obscure zone where Civil Society actors play a role both in theory and in practice. Theoretically, this study defends the existence of civil, anticivil and non-civil dimensions which are constantly in dispute within civil society, whether it is for resources or in the struggle in favor of or against the use of firearms. Empirically, this study claims that the agenda regarding firearms control is an extremely controversial matter for global and national governance. In addition, it has become the object of scientific research and public discussion largely due to the role of civil associations. This manifestation contributes to the though on the paradoxical relationship between Violence and Democracy, representing a decolonization of a traditionally insular topic belonging to the strategic military sphere of the State. The study therefore reconstituted the establishment of a global agenda analyzing the role of Global Civil Society with regard to both the characterization of firearms as real weapons of mass destruction and the subsequent subversion of the traditional hierarchy of Disarmament. Furthermore, the study compared the experiences of Brazil and Portugal in order to verify the internal and external variables that brought about national attention to firearms control as a necessary policy of National Security. In spite of the differences and similarities of both cases, the study found that this issue evokes a polarized dispute within the very field of Civil Society, particularly with regard to the discursive and juridical (de)construction of access to firearms as an individual civil right. Finally, the study suggests there is no way of guaranteeing the civil use of firearms and that a future challenge to this issue first and foremost depends on the correlation of forces established between Civil Society associations.